Perceived Security of Near Field Communication Chips in Financial Transfers – Case of Poland - Arkadiusz GRYKO; Ewa MATUSKA; Michał OLEJNICZAK (Communications of International Proceedings, 2021)
The aim of the article is to recognize the attitudes of Poles towards RFID and NFC technology using under-skin chips in financial transfers. In a theoretical part the history of electronic payments in Poland is outlined, explaining the socio-economic transformation after post-communistic period and its most critical moments. The RFID and NFC technology is assumed with the focus on its health, ethic and legal challenges and hesitations. In an empirical part the paper presents the analysis of authors’ own quantitative research in the format of a pilot study conducted on a sample (N=172) of Polish citizens of different age, education and place of living, dedicated to the topic of the acceptance RFID and NFC technology used in a form under-skin chips for financial transfers. Two hypotheses tested in a research were confirmed: Poles, although are open into new technology, have many doubts to NFC under skin chips, afraid the negative influence on NFC chips to their health as well as digital threats to their personal and finance data. But they are also aware they don’t have sufficient knowledge about that technology. In conclusions discovered pros and cons for implanting NFC chips are summarized.
Keywords: NFC chips; financial transfers; personal safety; health; ethical and legal issues of NFC